2020
DOI: 10.1094/pbiomes-08-19-0043-sc
|View full text |Cite
|
Sign up to set email alerts
|

Tapping Into the Cotton Fungal Phytobiome for Novel Nematode Biological Control Tools

Abstract: A number of fungi have been shown to have negative effects on plant-parasitic nematodes. Most of these fungi have been isolated from soil, plant roots, or nematodes themselves. Fungi associated with crops can provide a diverse pool of candidates to test for antagonistic effects against plant parasites and other stressors. We used a hierarchical two-tiered approach to evaluate the efficacy and repeatability of 55 strains of fungi originally isolated as foliar facultative endophytes from upland cotton (Gossypium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Eleven potential novel species belonged to the genera Amycolatopsis , Luteimicrobium , Glaciihabitans , Angustibacter , Massilia , Arthrobacter , Curtobacterium , Frondihabitns , Jatrophihabitans , Naumannella , and Tardiphaga , and one novel genus of the Dermacoccaceae family were dominant in H. serrate [ 70 ]. It is suggested that some fungal strains show antimicrobial activity against bacteria such as Bacillus cereus (Gram-positive) and E. coli (Gram-negative) and effectively decreased nematode infections in certain plant roots [ 71 , 72 ]. Endophytic fungi live in plants for a certain stage in their life cycle, but do not cause visible symptoms in plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven potential novel species belonged to the genera Amycolatopsis , Luteimicrobium , Glaciihabitans , Angustibacter , Massilia , Arthrobacter , Curtobacterium , Frondihabitns , Jatrophihabitans , Naumannella , and Tardiphaga , and one novel genus of the Dermacoccaceae family were dominant in H. serrate [ 70 ]. It is suggested that some fungal strains show antimicrobial activity against bacteria such as Bacillus cereus (Gram-positive) and E. coli (Gram-negative) and effectively decreased nematode infections in certain plant roots [ 71 , 72 ]. Endophytic fungi live in plants for a certain stage in their life cycle, but do not cause visible symptoms in plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some strains of Oidiodendron were reported to promote nitrogen uptake and plant growth [34], and exhibit metal tolerance [35]. Some strains of Cladosporium exhibited an antimicrobial activity against Bacillus cereus IIIM 25 (Gram positive) and Escherichia coli ATCC 25922 (Gram negative) [36], and effectively reduced the infection of nematodes in some plant roots [37]. The genera of Oidiodendron and Cladosporium might confer similar benefit upon the host H. serrata.…”
Section: Plos Onementioning
confidence: 99%
“…Root-knot nematodes, represented by Meloidogyne species, are globally ubiquitous and impact over 2000 plant species including economically important crops such as tomato, cotton, cucumber, melon, soybean and rice [ 104 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ]. Many fungal genera have been reported as having inhibitory effects on Meloidogyne species, including: Acremonium , Alternaria , Arthrobotrys , Chaetomium , Cladosporium , Clonostachys , Diaporthe , Drechslerella , EpichloĂ« , Epiccocum , Fusarium , Gibellulopsis , Melanconium , Metacordyceps , Monacrosporium , Neotyphodium , Paecilomyces , Phialemonium , Phyllosticta , Piriformospora , Purpureocillium , Talaromyces and Trichoderma [ 106 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Species from one or more of these genera have also been reported as having similar antagonistic effects towards other species of nematodes [ 106 ].…”
Section: Fungal Endophytes and Their Effects Against Plant-parasitic ...mentioning
confidence: 99%